Knowledge about organ and tissue transplantation among Medical students at a brazilian university (Research, Society and Development, 2023)
Objective: The objective of this study was to assess the level of knowledge among medical students regarding organ and tissue transplantation. Methodology: A total of 207 medical students from the University of Vassouras in the state of Rio de Janeiro were included in this study, with data collected between 2021 and 2022. An anonymous online questionnaire consisting of 26 questions was used to gather information on the students' epidemiological profile and their knowledge of organ donors, the transplantation process, and its management. Descriptive analysis was performed on the obtained results, and the relationship between variables was evaluated using the chi-square test for association. Ethical approval was obtained from the institution's Research Ethics Committee under opinion number 4,686,474. Results: Among the participants, 86.9% were committed organ donors, with 70.4% having already communicated their decision to their families. A total of 11.2% of the students had not yet made a decision, while 1.9% decided not to donate. The overall average score for correct responses on the questionnaire was 46.0%, with a higher rate of correct responses observed for questions related to the definition of brain death. Statistical analysis revealed a significant association between the percentage of correct responses and the stage of the medical course, but no significant association with gender or age was found. Conclusion: The study revealed a suboptimal level of knowledge among medical students regarding organ and tissue transplantation, with less than half of the questions answered correctly. These findings emphasize the need for enhanced education on this topic and the implementation of lectures, training programs, and campaigns in universities to better equip healthcare professionals in identifying potential organ donors in the hospital setting. Further investigations are warranted to explore this topic and determine if similar knowledge gaps exist in other Brazilian universities.